Garuda Indonesia restructuring strategy due to company performance enhancement - Imam Ozali (Junal Ilmu Manajemen, 2023)
Garuda Indonesia restructuring objective is to address the financial and operational problems faced by the company, as well as ensure long-term business sustainability. The restructuring strategy carried out by Garuda Indonesia was to overcome the various problems it faced, namely a significant financial decline, including increasing debt, high operational costs, and reduced revenue. To deal with this situation, Garuda Indonesia adopted several strategic steps. The method used in this study is a descriptive method, which is a research method used to systematically describe the facts or characteristics of a phenomenon faced by Garuda Indonesia through the collection of relevant public data and information about the steps taken by Garuda Indonesia in its restructuring efforts. This method aims to provide a comprehensive picture of the restructuring strategy undertaken by Garuda Indonesia. The first step is internal improvement, in which the company conducts a thorough evaluation of the organizational structure, reducing costs, and improving operational efficiency. In this process, Garuda Indonesia restructured its human resources, reduced the number of employees, and improved its management and control systems. The results of the restructuring carried out by Garuda Indonesia cannot be assessed as a whole because it is still in the implementation process. However, the restructuring measures that have been taken demonstrate the company's commitment to overcoming the problems encountered and strengthening their position in the market.